2019
DOI: 10.1002/pssb.201800418
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur‐Doped Phosphorene as a Promising Anode for Na and K‐Ion Batteries

Abstract: In the present work, a novel anode candidate – sulfur‐doped phosphorene – for the Na‐ion batteries and K‐ion batteries has been proposed. The doped geometry, Na/K adsorption energy, average open‐circuit voltage, specific capacity, Na/K diffusion barriers, and charge transfer on sulfur‐doped phosphorene sheets are investigated through the way of adopting ab initio periodic quantum chemical method. The results demonstrate that, toward the directions of armchair and zigzag, the energy barriers of Na/K diffusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…These values are close to the previously reported values for S-doped BP, although the S concentrations differ in our work. 40,41 The presence of the S atom causes the adjacent P atom in the lower layer to move slightly away from the surface, so the distance between the two layers around the S atom increases slightly to 2.20 Å.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are close to the previously reported values for S-doped BP, although the S concentrations differ in our work. 40,41 The presence of the S atom causes the adjacent P atom in the lower layer to move slightly away from the surface, so the distance between the two layers around the S atom increases slightly to 2.20 Å.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results, this surface could be a promising anode for Na and K-ion batteries. [38][39][40] The effect of BP surface doping with Ca, Ti, S or Se atoms on the adsorption behavior of 2,3,7,8-tetrachlorodibenzo-p-dioxin has been investigated by DFT calculations. The results have shown that Ca-doping improves the interaction while Se-doping reduces it and doping with Ti or S atoms does not have a great effect on this interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Compare with the pristine phosphorene, the anisotropy is also strengthened after sulfur-doping, where the diffusion energy across the armchair and zigzag directions of single-layered phosphorene had an increasement of 0.76-0.81 eV and a decreasing of 0.76-0.18-0.14 eV, respectively. [252,253] Furthermore, a safety voltage operation of 0.61 V was obtained for Na storage on the phosphorene monolayer. A strong sp hybridization of S and P can significantly change the electronic structure of phosphorene and enable it to become metallic.…”
Section: Phosphorenementioning
confidence: 96%
“…Recently, sulfur-doped phosphorene as an anode of SIBs has been proposed by using ab initio DFT investigations. [252] Na adsorption energy is about 1.56 eV which derives from stable adsorption with S-doped phosphorene sheet endowing a ultralow diffusion barrier of 0.14 eV. Compare with the pristine phosphorene, the anisotropy is also strengthened after sulfur-doping, where the diffusion energy across the armchair and zigzag directions of single-layered phosphorene had an increasement of 0.76-0.81 eV and a decreasing of 0.76-0.18-0.14 eV, respectively.…”
Section: Phosphorenementioning
confidence: 99%
“…48 It has been reported that vacancies and Stone–Wales defects can effectively enhance the adsorption and diffusion of Na on monolayered BP, 49 and doping has impacts on the performance of SIBs. 50 However, previous theoretical studies have mainly focused on Na adsorption in BP, volume change in Na insertion/desorption and the impact caused by the defects of BP at ground state, and these studies have not taken temperature into account. In fact, the structural stability of the BP systems at room temperature is very important for practical applications.…”
Section: Introductionmentioning
confidence: 99%